2022
DOI: 10.1186/s13047-022-00591-y
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating ‘Green Podiatry’ into your clinic, and into your life

Abstract: Background This commentary outlines practical ways of positively incorporating green podiatry, foot health, physical activity benefits, and relevance to climate change into the clinical setting as Conference of Parties (COP27) approaches. Recent reports from the Intergovernmental Panel on Climate Change, the World Economic Forum, and undergraduate curricula concerns, are presented. Main body Climate change is irrefutable, and as health professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…We can take a 'green L.E.A.P.' 28 to educate ourselves and our patients about 'big picture' health. This is especially important for younger colleagues, to allay eco-anxiety 33…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can take a 'green L.E.A.P.' 28 to educate ourselves and our patients about 'big picture' health. This is especially important for younger colleagues, to allay eco-anxiety 33…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 summarises the three Green Podiatry pillars. Our everyday actions can contribute to environmental and social sustainability 4,8,28 .…”
Section: Everyday Actionmentioning
confidence: 99%
“…In 2020, the COVID-19 pandemic presented an opportune movement to address climate change, leading to 47% of Australians showing increased concern about climate change [ 3 ]. Furthermore, it was observed that this concern about climate change surpassed that of COVID-19 by three times [ 3 ]. Over time, the pandemic was perceived as an exacerbating factor of the climate crisis, creating an ongoing and evolving issue.…”
Section: Introductionmentioning
confidence: 99%
“…Green podiatry, as part of sustainable healthcare, guides us to be responsible consumers of energy and products and to reduce emissions in the workplace. However, Spanish podiatrists are still unaware of these concepts and therefore do not apply them to improve the planet’s overall health [ 3 ].…”
Section: Introductionmentioning
confidence: 99%